Popular Resistance to Legal Authority in the Upper St. Francis District of Quebec: The Megantic Outlaw Affair of 1888-89 - Little, Jack (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
This essay attemps to explain why the Scots Canadians of Québec's upper St. Francis district protected the fugitive, Donald Morrison, against the full force of the law in 1888-89. It rejects the proposition that ethnic tensions were a major factor, arguing instead that Morrison conforms to Eric Hobsbawm's definition of a primitive rebel. With the railway undermining the local subsistence-oriented economy and encouraging families to migrate from the district, the Highland community was facing a survival crisis which it would ultimately lose. The Megantic Outlaw affair therefore represented a final defiant and largely symbolic stand on the part of a tightly-knit rural community succumbing to the forces of industrial capitalism.